Pathogenesis of Rickets and Osteomalacia in Familial Hypophosphataemia. Issue 247 (June 1971) - Condon, J. R.; Nassim, J. R.; Rutter, A.
Abstract : Calcium and/or phosphate tolerance tests were performed on patients with familial hypophosphataemia, normal control subjects, and patients with vitamin D deficient osteomalacia. Intestinal calcium absorption was similar in patients with familial hypophosphataemia and control subjects. The phosphate tolerance test, which is known to be `flat' in patients with familial hypophosphataemia, was normal in patients with vitamin D deficient osteomalacia. These findings suggest that rickets and osteomalacia in familial and some cases of non-familial hypophosphataemia are unrelated to abnormal metabolism of vitamin D. This hypothesis is supported by the fact that intestinal calcium absorption as measured by calcium tolerance test is normal in familial hypophosphataemia. It is suggested that the primary abnormality in familial hypophosphataemia is a partial metabolic block in the intestinal absorption and renal tubular reabsorption of phosphate.